From the shallows to the depths: a new probe set to target ultraconserved elements for Decapoda and other Malacostraca - Geburzi, Jonas C.; Rodríguez-Flores, Paula C.; Derkarabetian, Shahan; Giribet, Gonzalo (Frontiers in Marine Science, 2024)
Introduction Since its introduction about a decade ago, target enrichment sequencing of ultraconserved elements (UCEs) has proven to be an invaluable tool for studies across evolutionary scales, and thus employed from population genetics, to historical biogeography as well as deep-time phylogenetics. Here, we present the first probe set targeting UCEs in crustaceans, specifically designed for decapods and tested beyond decapods in other malacostracan lineages. Methods Probes were designed using published genomes of nine decapod and one peracarid species, as well as raw Nanopore long reads of one additional brachyuran species. The final probe set consists of about 20,000 probes, targeting 1,384 unique UCE loci. We compiled a dataset across Malacostraca,as well as datasets of a deep-sea squat lobster genus, and an intertidal mangrove crab species, to test the probe set at different phylogenetic levels (i.e., class, order, genus, within species). Results Final mean UCE recovery from fresh samples across Malacostraca was 568 loci, with up to 847 and 658 loci recovered from decapod and non-decapod species, respectively. Final mean recovery from fresh samples in the genus- and within species-level datasets was 849 and 787 loci, respectively. Up to several hundreds of UCEs were recovered from historical museum specimens (10 to > 150 years old), that were included in all datasets. UCE-based phylogenies largely reflected the known relationships of the included taxa, and we were able to infer population differentiation based on >600 SNPs extracted from the species-level dataset. Discussion Our results showcase the versatility of this UCE probe set, yielding informative data from phylogenetic as well as population-genetic datasets. They demonstrate once more that UCEs are a promising technique for leveraging museum specimens for genomic studies, and overall highlight the probe set's potential for crustacean evolutionary studies.